CLINICAL CASE OF MULTIMODALITY TREATMENT OF METASTATIC BLADDER CANCER - A. V. Lykov; V. G. Znobishchev; I. B. Popov; A. A. Keln (Сибирский онкологический журнал, 2020)
Background. Bladder cancer is one of the most common cancers. Non-muscle-invasive bladder cancer is characterized by the high frequency of recurrence after radical treatment (up to 50–60 %), and muscle-invasive bladder cancer has a lower recurrence rate (30 %). Primary metastatic bladder cancer (Bc) is detected in 10–15 % of cases. transurethral resection of the bladder is the main treatment modality for non-muscleinvasive Bc. For muscle-invasive Bc, radical cystectomy is the curative treatment of choice. chemotherapy is used for the treatment of metastatic Bc. the role of surgery for metastatic Bc has not yet been determined. there are only a few reports regarding multimodality treatment including metastasectomy for metastatic Bc. Case description. We present a clinical case of successful treatment of metastatic Bc, we used surgery, radiotherapy, chemotherapy and x-ray endovascular technologies. the patient is alive with no evidence of disease. Conclusion. Our findings are consistent with other reports which indicate that the removal of metastases in patients with advanced urothelial carcinoma is technically feasible and can be safely performed. Metastasectomy can have a positive effect on survival. However, metastasectomy remains the subject of clinical studies, and should be recommended only for patients a good response to systemic therapy.